Interrupting a mitochondrial DNA–driven innate immune circuit attenuates hepatic tissue remodeling and fibrotic architecture in experimental steatohepatitis - Rabab S. Hamad; Sura Akram Mohammed; Waseem Ali Hasan; Norhan Ahmed AbuoHashish; Sherin Refat El Afify; Mohamed A.M. Ali; Alaa Eldin Ahmed Mohamed; Attalla F. El-kott; Mohammed A. AlShehri; Kareem Morsy; Alshaimaa A. Farrag; Karem Mohamed Salem; et al. (Tissue and Cell, 2026)

Growth, Digestive Enzyme Activities, Antioxidant Properties, and Intestinal Histology of Nile Tilapia ( Oreochromis niloticus ) Fed Diets Supplemented With Garlic Nanoparticles - Sami Alaa Sami; Ashraf Y. El‐Dakar; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Mohammed F. El Basuini; Shymaa M. Shalaby; Mohamed M. Rashad; Simon J. Davies; Mohamed F. Abdel‐Aziz (New Zealand Journal of Marine and Freshwater Research, 2026)
This work may be the first of its kind to assess the effects of varying inclusion levels of garlic nanoparticles (NPsG) as feed additives on growth and physiological indices in Nile tilapia ( Oreochromis niloticus ). Garlic contains an organosulfur compound called allicin that can promote growth and strengthen the immune system by stimulating appetite and the intestinal flora, thus enhancing energy utilization. Nanotechnology provides new tools in aquaculture nutrition, including increasing the ability of fish to absorb nutrients rapidly and the effectiveness of feed additives by enhancing their bioavailability compared to their bulk form. Five concentrations of NPsG (0, 150, 300, 600, or 1200 mg/kg) were evaluated by their addition to a basal diet (30% crude protein). 225 juveniles with an initial weight of 3.92 g ± 0.42 (SE) were randomly divided into 15 cages of polyethylene. The cage had dimensions of length: width: height (100:40:60 cm) and was continuously aerated using a 2 HP air blower with air stones. After 42 days, feeding results revealed that NPsG supplementation had significant effects ( p < 0.05) on improving the performance, physiological indicators, and histomorphometry of the intestine in comparison with the control. Fish that were fed a dietary supplement of 600 mg/kg of NPsG exhibited the highest specific growth rate (2.80%/day), along with elevated levels of intestinal enzymes lipase, amylase, and proteases (212.40, 15.00, and 318.60 U/g of intestine, respectively) and the lowest malondialdehyde level (81 nmol/g of liver tissue). This group was followed by fish fed a diet of 300 mg/kg of NPsG, which did not significantly differ from those fed 600 mg/kg of NPsG in superoxide dismutase, total antioxidant capacity, and histomorphometry of intestine villi. Finally, the complete dose–response recommendation (benefit at 300–600 mg/kg and detriment at 1200).

Toward Eco-Friendly Solutions for Plastic Pollution: Insights into Polyethylene Biodegradation - Alaa F. Elsayed; Dina H. Amin; Hassan M. Gebreel; Ihsan Mahasneh; HebatAllah I. Youssef (Water, Air, & Soil Pollution, 2026)

Chitosan reduces methane emissions and alters the phylogenetic affiliation of sampled methanogens in in vitro rumen fermentation - Marwa F. A. Attia; Amr E. El-Nile; Alaa M. A. Gad; Mohamed S. Moharam; Ahmed E. Kholif; Raed A. Aburawash; Elsayed E. Hafez; Sobhy M. A. Sallam (Environmental Science and Pollution Research, 2026)